PENINGKATAN HASIL BELAJAR KOGNITIF SISWA MENGGUNAKAN METODE PRATIKUM PENERAPAN Al2(SO4)3 TERHADAP MATERI KOLOID - Yantonius Tafonao; Adilah Wirdhani Lubis; Dian Nirwana Harahap (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2024)
The research aims to determine the increase in students' cognitive learning outcomes through a demonstration of the use of Al2(SO4)3 for dyeing fabric on colloidal materials. The method in this research is one group design, namely research is only carried out in one class. Data collection techniques used field observation, interviews, pretest and posttest as well as response questionnaires. The results of this research showed that the average pretest score before treatment was 53.68%, while after treatment there was an increase with an average posttest score of 81.04% with a pretest and posttest N-Gain index of 0.5 in the medium category and a percentage of 58%. Based on the results of this research, the application of Al2(SO4)3 for effective fabric coloring can increase students' cognitive learning outcomes.